2014
DOI: 10.5812/pedinfect.15930
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Adenovirus Infection Among Children With Acute Respiratory Disease During 2010-2012 in Shiraz, Iran

Abstract: Background: Acute viral respiratory infection (ARVI) is a common cause of morbidity and mortality especially in pediatric patients. Among important respiratory pathogens, adenovirus is a most prevalent cause of upper and lower respiratory tract infection. Objectives: The aim of the present study was to determine the prevalence of adenovirus infection in pediatric patients with respiratory symptoms. Patients and Methods: This cross-sectional study was carried out from November 2010 to February 2012. An in-house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(36 reference statements)
1
5
1
Order By: Relevance
“…In total of 400 patients, 37 cases (9.2%) were infected with adenovirus that the frequency was similar to study of Echavaria and his Colleagues in Argentina [14] and that is lower than the frequency of 14.4% and 22% reported by another study from Iran [1] [15] [16] and several parts of the world including Oman (15%), Kenya (14%), Korea (10.3%), Canada (7.73%), Brazil (7.1%), Australia (7.3%), Hung Kong (5.3%), Mejia (5.2%), and China (4.9%) [1] [17] [18].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In total of 400 patients, 37 cases (9.2%) were infected with adenovirus that the frequency was similar to study of Echavaria and his Colleagues in Argentina [14] and that is lower than the frequency of 14.4% and 22% reported by another study from Iran [1] [15] [16] and several parts of the world including Oman (15%), Kenya (14%), Korea (10.3%), Canada (7.73%), Brazil (7.1%), Australia (7.3%), Hung Kong (5.3%), Mejia (5.2%), and China (4.9%) [1] [17] [18].…”
Section: Discussionsupporting
confidence: 78%
“…Different factors are involved including respiratory syncytial virus (RSV), influenza virus, parainfluenza virus (PIV), rhinovirus (RV), and human adenovirus (HAdV) [1].…”
mentioning
confidence: 99%
“…The statistical analysis revealed a significant difference between groups (X 2 = 11.064; P<0.01), where the viral DNA was detected in approximately a third (28.08%) of the total study groups (Table 3-1). The frequency of HAdVs positive cases in our study was higher for most studies than that reported in the Middle East such as Turkey 26.2% [17], Iran 14.4-22% [18][19][20], Israel 18.3% [21], Saudi Arabia 17.4% [22]. Other parts of the world reported different values like Kenya 14% [23], Korea 10.3% [24], Australia 7.3% [25], and Peru 6.2% [26].…”
Section: Resultscontrasting
confidence: 49%
“…Only limited studies showed significant differences between male and female in which the infectious rate of HAVs in males were higher than females [26,35]. Also, Moattari et al, a study in Iran showed that the infectious rate of HAV was high in females than in males [20].…”
Section: Molecular Diagnosis Of Human Adenovirus In Children With Uppmentioning
confidence: 99%
“…1,2 Adenovirus is the greatest reason for upper and lower respiratory tract disease, 3 and constitutes 5-8% of all Respiratory tract infections (RTIs) in neonate and children. 3,4 Other research showed that Adenovirus infection range between 5 to 15% of upper and lower RTIs in hospitalized children for respiratory disease. 5,6 Adenovirus (AdV) is considered one of the greatest public viruses causing RTIs in immunocompetent adults and elderly persons.…”
Section: Introductionmentioning
confidence: 99%